COMPUTER SYSTEMS IN THE EDUCATIONAL PROCESS (Innovative professional education, 2025)
This article is devoted to teaching programming and observing security when working with computer systems during wartime. The use of computer systems in the educational process is now gaining particular importance. We have occupied territories, and there are our people there, in particular, students, who need to be taught, and this can only be done remotely
Keywords: computer systems, security, teaching programming, motivation, learning